Phytochemical and Pharmacological Activity of Withania somnifera (L.) Dunal - Tarun Halder; Biswajit Ghosh (International Journal of Economic Plants)
Withania somnifera (L.) Dunal is commonly called as Ashwagandha and it belongs to the family Solanaceae. It is an eminent medicinal plant widely used in the treatment of many clinical conditions in Indian subcontinent. It has natural source of withanolides (steroidal lactones) which are used as ingredients in many formulations prescribed for a variety of diseases. It has important medicinal capacity which has been used either single or in combination with other drugs in Unani as well as Ayurvedic system of medicine for centuries. Several therapeutic actions such as anti-inflammatory, neurostimulatory, hepatoprotective, anti-cancerous, immune-modulator and antioxidant activity. Observance in view the medicinal properties of Ashwagandha an effort has been made to explore various dimensions of the drug including phytochemical and pharmacological studies carried out on this herb. Pharmacological activity of W. somnifera needs number of scientific justification which would be helpful for the further future research.